Precipitation modulates the net effect of solar radiation on litter decomposition and CO2 emission - a meta-analysis - Liu, YaLan; Li, Lei; Wang, ShiQi; Li, Xiangyi (Frontiers in Plant Science, 2023)
Introduction Solar radiation plays a crucial role in the decomposition of litter and the cycling of nutrients. Previous studies have investigated that the net effect of solar radiation on litter decomposition depends on the balance of its facilitative and inhibitory effects on microbial activity; however, a gap in understanding the mechanism by which precipitation affects the net effect of solar radiation and the mechanism of litter decomposition on a global scale was observed. Methods In addressing this gap, a comprehensive meta-analysis of 351 data points from 37 published studies was conducted to estimate the sole radiation effect and interactive effect of solar radiation and precipitation on a global scale, as well as how they vary at different precipitation levels. In addition, the importance of influential factors regulating the net effect of solar radiation on litter decomposition was assessed to identify the key drivers of the response of mass loss to solar radiation at different precipitation levels. Results Our findings indicated that solar radiation largely regulates litter decomposition, and the direction and magnitude are potentially dependent on the precipitation regime. In addition, solar radiation significantly increased mass loss and decreased the nutrient remaining. Furthermore, the effects of solar radiation on mass loss, C remaining, and N remaining were found to be similar among areas with precipitation levels below 200 and above 800 mm and greater than in areas with precipitation levels between 200-400 mm and 400-800 mm. The effect of solar radiation on CO2 emissions varied from 13.97% when precipitation was below 200 mm to −0.707% when precipitation was between 200 and 400 mm. Conclusion Climatic factors determine the response ratio of mass loss to solar radiation in arid lands, whereas the initial litter characteristics have a great influence on the response of mass loss to solar radiation in ecosystems that are not moisture limited. The effect of precipitation on the photodegradation mechanism of litter was primarily achieved by influencing the decomposition of lignin, and the main effect of solar radiation on litter decomposition will shift from the positive effect of “photopriming” to the negative effect of “microbial inhibition” with the increase of precipitation. Our findings can provide a comprehensive understanding of litter decomposition patterns on a global scale, and our results showed that CO2 emissions from photodegradation will be lessened by precipitation, which is important in predicting CO2 emission and separating sources of CO2 under future increasing precipitation scenarios, particularly in arid lands.